Vibration actuator, lens barrel and camera - MORIOKE TOSHIKAZU (2012)
To provide a vibration actuator having good driving performance even when miniaturized, and a lens barrel and camera provided with the same. A first aspect of the present invention is to provide a vibration actuator comprising, an electromechanical conversion element, having a first joining face, and which is subject to excitation, an elastic body having a second joining face which is joined to the first joining face, and a driving face which gives rise to vibration waves as a result of said excitation, and a relative moving member, having a contact face which is in pressure contact with the driving face, which is driven by the vibration waves, and which moves relative to the elastic body, wherein an outer shape of said first joining face has a shape which differs from an outer shape of said contact face.